The use of community connecters to increase black community involvement in research: a case example - Joanne Ellis; John Alex Muyita (Research Involvement and Engagement)
Abstract This paper presents a case example of an innovative approach to increase the involvement of underrepresented groups in research using community connectors. We focus on the development and implementation of a strategy to engage young Black individuals in Greater Manchester in mental health research. The paper outlines the role and methodology of community connectors, reflects on key challenges and learning, and provides recommendations to inform future Public, Community Involvement and Engagement (PCIE) work. We conclude with a discussion of outcomes and impact, including practical considerations for sustainable and inclusive engagement practices.